Perlindungan Konsumen terhadap Peredaran Kosmetik yang Mengandung Zat Berbahaya di Kota Denpasar - I Gede Tirtayasa; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Nowadays, the trend of beauty products is growing rapidly among the people, which causes the emergence of cosmetic business actors who act fraudulently. Licensing of cosmetic products is of course very important because with a permit from the government, it can be ascertained that the product is safe to use. This study aims to determine consumer protection against the circulation of cosmetics containing hazardous substances in the city of Denpasar and to find out the responsibility of business actors for the circulation of cosmetics that harm consumers. This research was conducted to collect data at the Department of Industry and Trade of Denpasar City and YLKI Bali with interview and documentation techniques. The data analysis used is qualitative data analysis. The results of the study indicate that legal protection for consumers for the distribution of cosmetics that harm consumers is carried out by every element involved based on Law No. 8 of 1999 concerning Consumer Protection and Regulation of the Indonesian National Food and Drug Administration No. HK.00.05.4.17.45 concerning Cosmetics. The responsibility of business actors for the circulation of cosmetics that harm consumers is in the form of compensation given in the form of refunds or replacements in the form of goods. If this is found to be intentional, the business actor may be subject to sanctions. There are two types of sanctions given if business actors are proven to produce dangerous cosmetics. The first is administrative sanctions in the form of fines, and criminal witnesses in the form of confinement or imprisonment. The form of sanctions given is adjusted to the level of producer error and losses experienced by consumers.